2014
DOI: 10.3389/fonc.2014.00006
|View full text |Cite
|
Sign up to set email alerts
|

Gene Expression Analysis in Ovarian Cancer – Faults and Hints from DNA Microarray Study

Abstract: The introduction of microarray techniques to cancer research brought great expectations for finding biomarkers that would improve patients’ treatment; however, the results of such studies are poorly reproducible and critical analyses of these methods are rare. In this study, we examined global gene expression in 97 ovarian cancer samples. Also, validation of results by quantitative RT-PCR was performed on 30 additional ovarian cancer samples. We carried out a number of systematic analyses in relation to severa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
68
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 76 publications
(73 citation statements)
references
References 41 publications
3
68
0
Order By: Relevance
“…Most of the overrepresented biological processes (p50.05) were related to regulation of angiogenesis and blood vessel formation, peptidase activity, signaling, cell functions, such as motility, cell cycle and death, cell shape, coagulation and communication, suggesting an involvement of TSP-1 in these aspects of ovarian tumor progression (Figure 4). The expression of TSP-1 was also analyzed in a large external gene expression dataset, retrieved from GEO (GSE63885, NCBI database), comprising 101 ovarian cancer surgical samples (31). In these clinical samples, TSP1 resulted slightly differentially expressed according to histotype (Kruskal-Wallis test, p ¼ 0.059), with higher expression in serous versus endometrioid cancers ( Figure 5), as already observed in our PDX cohort.…”
Section: Resultssupporting
confidence: 53%
“…Most of the overrepresented biological processes (p50.05) were related to regulation of angiogenesis and blood vessel formation, peptidase activity, signaling, cell functions, such as motility, cell cycle and death, cell shape, coagulation and communication, suggesting an involvement of TSP-1 in these aspects of ovarian tumor progression (Figure 4). The expression of TSP-1 was also analyzed in a large external gene expression dataset, retrieved from GEO (GSE63885, NCBI database), comprising 101 ovarian cancer surgical samples (31). In these clinical samples, TSP1 resulted slightly differentially expressed according to histotype (Kruskal-Wallis test, p ¼ 0.059), with higher expression in serous versus endometrioid cancers ( Figure 5), as already observed in our PDX cohort.…”
Section: Resultssupporting
confidence: 53%
“…However, a reverse was observed in cancers such ovarian, osteosarcoma, B-Cell lymphoma, and lung (Bild et al, 2006; Kuijjer et al, 2012; Lisowska et al, 2014), specifically low SR-B1 correlated with poor survival. Given the complexities involved in the regulation of SR-B1 expression it is difficult to hypothesize regarding mechanism(s) involved in the observed variations of SR-B1 expression in relation to patient survival.…”
Section: Sr-b1 As a Predictor Of Tumor Prognosis And Survivalmentioning
confidence: 99%
“…Using the publicly released ovarian cancer dataset (GSE9891)15 from the Gene Expression Omnibus (GEO) database, we identified a signature including seven lncRNAs associating with survival, and proposed a risk score formula based on their expressions to predict the patient survival. The prognostic risk score model was further validated in the cohorts GSE26193 and GSE63885 16,17. Our findings indicated that the seven-lncRNA signature can serve as a strong prognostic biomarker for ovarian cancer.…”
Section: Introductionmentioning
confidence: 78%